On the intrinsic relations of correlations in some systems of linear structural equations - Balabanov, O.S. (Reports of the National Academy of Sciences of Ukraine, 2016)
For a probabilistic linear model of cyclic structure with four variables, we prove two simple inequality-type constraints on the set of correlations. Each of the inequalities (comprising two and three correlations, respectively) facilitates the rejection of the basic model in favor of an alternative model, which differs in that it contains an additional "diagonal" connection.